Protective factors against preterm infants to develop significant patent ductus arteriosus - Hsiao-Wen Huang; Chih Lin; Kai-Hsiang Hsu; Shih-Yun Hsu; Tze-Yee Mok; I-Hsyuan Wu; Mei-Yin Lai; Reyin Lien (Elsevier, 2021)
Background: Identifying preterm infants with a higher likelihood of spontaneous patent ductus arteriosus (PDA) closure would be desirable. This study aimed to examine daily PDA status during the first week of life for very low birthweight (VLBW, <1500 g) preterm infants and to develop a scoring system to predict spontaneous PDA closure. Methods: We enrolled VLBW infants admitted between January 2016 and January 2017 and performed daily echocardiographic screening for PDA existence. Oxygen index (OI, mean airway pressure × fraction of inspired oxygen/partial pressure of arterial oxygen) was applied to represent the respiratory condition. Results: A total of 215 VLBW infants were enrolled, and the accumulative incidence of spontaneous PDA closure by age 1 week was 80%, 70%, and 34% for infants born of gestational age (GA) ≥30, 28-29, and ≤27 weeks, respectively. Of these 215 infants, 184 infants entered the second phase to establish the scoring system. Infants with spontaneous PDA closure were more mature (GA 29.2 ± 2.3 vs. 26.9 ± 2.3 weeks, p < 0.001), had lower OI (2.8 ± 2.2 vs. 5.6 ± 5.3, p < 0.001) and were less likely to need endotracheal intubation (23% vs. 68%, p < 0.001). Using the receiver operating characteristics curve, OI <2.5 was determined favoring higher PDA closure incidence. The score was calculated based on the odds ratio generated in multiple regression: 4, 3 and 1 points for GA ≥30, 28-29 and ≤27 weeks, 2 and 1 points for OI <2.5 and ≥2.5, and 3 and 1 points for without and with endotracheal intubation. Using score ≥6 to predict PDA closure, the sensitivity and specificity were 0.77 and 0.72. Conclusion: A score made up of GA, OI and need for intubation was proposed to predict spontaneous PDA closure by age 1 week, which could be helpful to clinicians in the management of PDA in preterm infants.